Current ongoing monitoring and prospects of prediction of the confectionary products state with new capacitive transducers - Tarasenko, Sergiy; Kolomiets, Dmitro; Galushko, Mykola (My University, 2013)
The capabilities of new high-precision three-contact capacitance transducers for monitoring and predicting the state of confectionery on their dielectric permittivity and electrical conductivity was described.
Keywords: прецизійний ємнісний датчик; триконтактні; діелектрична проникність; поточний контроль; стан виробів; прецизионный емкостный датчик; трехконтактные; диэлектрическая проницаемость; поточный контроль; состояния изделий; precision capacitive sensor; three-contact; dielectric constant; current monitoring; products state; кафедра електропостачання і енергоменеджменту